Evaluación de la resistencia adhesiva de una resina compuesta a dentina tratada con clorhexidina y terapia fotodinámica. Estudio in vitro - Huarote Fernández, Joaquín Enrique (2023)
Introduction: Photodynamic therapy consists of the application of a light with an adequate wavelength on the cavities prior to the application of a photosensitizing agent, with the purpose of eliminating remnants of microorganisms remaining after instrumentation. Objective: Evaluate the adhesive resistance to dentin treated with 2% chlorhexidine and photodynamic therapy with a 660nm diode prior to the insertion of composite resin. Materials and Methods: In this in vitro experimental study, 60 bovine mandibular incisors were collected, after dentin wear, the samples were divided into 3 groups, with 20 samples per group: control group (no therapy was applied), 2% chlorhexidine, and 660nm diode laser (photosensitizer: methylene blue). Adhesive strength test was measured by shear test compared to kruskall-wallis test and post-hoc pairwise comparison. Results: The average values from highest to lowest result with the CHX (14.82 ± 3.14), followed by the 660nm diode laser (14.77 ± 4.02) and the control group (9.25 ± 1.16). Similar groups of 660 nm diode laser and 2% CHX changed values (P>0.05), but significantly higher than the control group (P<0.001). Conclusion: Photodynamic therapy increased adhesive resistance as well as chlorhexidine, both therapies presented an increase in adhesive resistance compared to the control group.